Meteorological validation of chironomids as a paleotemperature proxy using varved lake sediments. (June 2017) - Luoto, Tomi P; Ojala, Antti EK
In order to improve the reliability of climate models in their projections for the future, spatially and temporally detailed paleoclimate proxy data are needed. In this study, we examined annually laminated sediments from Lake Nurmijärvi (Finland) for their fossil Chironomidae assemblages over a time period with available meteorological observational data (since 1830s). In doing so, we correlated chironomid-based inferences of summer air temperatures against instrumentally measured values using two different reconstruction approaches, namely, calibration-in-space (CiS, multilake training set) and calibration-in-time (CiT, calibration of time series data against meteorological data). The results showed that the principal variability in fossil chironomid assemblages in the sediment core corresponded to the measured air temperatures. In addition, the temperatures reconstructed using CiS ( R = 0.38, p = 0.014) and CiT ( R = 0.51, p = 0.001) correlated significantly with the meteorological data; however, the CiS approach showed higher variability and larger differences against the instrumentally measured values. A significant lag of on average 4–8 years was also found in the chironomid response to observed temperature change that is, nevertheless, much shorter time span than with some other paleoclimate proxies. The results verify the usability and sensitivity of chironomids as a paleoclimate proxy in the Nurmijärvi varved sediment record with the potential value of an exceptionally well-resolved downcore record of the Holocene climate change in the future. The CiT approach can potentially provide accurate paleotemperature estimates at the late-Holocene scale, but the CiS approach may be more useful at longer timescales if the community compositions change significantly from those occurring during the calibration period of the CiT.